Optimalisasi Pendidikan Agama Islam Dalam Membangun Jiwa Empati Siswa MTS Zakiyun Najah Sei Rampah - Diana Diana; Susanti Nirmalasari; Irwansyah Irwansyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore the optimization of Islamic Religious Education (IRE) in fostering students' empathy at MTs Zakiyun Najah. Empathy is one of the essential values that should be instilled from an early age to shape students' social sensitivity and moral responsibility. In an era marked by growing individualism and the erosion of prosocial behavior among adolescents, the role of religious education becomes increasingly vital. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation. The findings indicate that the IRE learning process at MTs Zakiyun Najah is implemented not only through theoretical delivery of material but also through contextual learning, exemplary behavior by teachers, and involvement in social-religious activities such as charity, group discussions, and school-wide religious programs. Teachers integrate empathy values through reflective practices, character journals, and social engagement to strengthen students’ awareness of others’ feelings and needs. Furthermore, the school’s religious environment supports the internalization of Islamic values that promote care, altruism, and mutual assistance. This study concludes that optimizing Islamic Religious Education plays a significant role in developing empathetic behavior among students, helping them become morally conscious and socially responsible individuals.